Practice of compost use in urban farming: Opportunities and constraints in the West Region, Cameroon - Kongnso, Moye Eric (International Journal of Environment, Agriculture and Biotechnology, 2024)
Urban agriculture is an ancient economic activity that sustains urban livelihoods. Composting as an alternative method of waste treatment and compost use in urban farming has led to sustainable practices. This paper sets to examine the opportunities and barriers of compost use under the lens of the Social Practice theory. Adopting a mixed methods approach, data was collected during a questionnaire survey of 265 households purposively selected from the urban and peri-urban quarters, eleven (11) in-depth interviews with stakeholders and a focus group discussion with compost users. Quantitative data from questionnaires were analyzed statistically using SPSS while qualitative data from interviews and focus group were treated using content and thematic analysis with the help of Atlas.ti. Findings revealed that compost use practices are favored by the availability of compost and technical assistance provided to farmers. Municipal compost production has increased from 60tons to 600tons per year over a period of 10 years and private composting is greatly improved. Nevertheless, small scale famers have constraints which are technical, experience and knowledge, financial, institutional and policies. Farmers in the peripheries (45%) tend to compare compost with mineral fertilizers and are reluctant to change their old practices. State extension services promote mineral fertilizers over compost but farmer-to-farmer experience sharing has informed practices. The existing regulatory landscape has not encouraged compost use and traditional practices persist. Adopting sustainable practices require policies that prioritize compost use.